SARS-CoV-2 and dialysis: humoral response, clinical and laboratory impacts before vaccination - Santos, Alanna Calheiros (2024)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório Brasileiro de Referência em Hepatites Virais. Rio de Janeiro, RJ, Brasil.